Detection of Plantaricin-Encoding Gene and Its Partial Purification in Lactobacillus plantarum BP102 - Elsa Mega Suryani; Yoga Dwi Jatmiko; Irfan Mustafa (UIN Sunan Gunung Djati Bandung, 2023)
Lactobacillus plantarum BP102 isolated from garlic bulb tissue has probiotic properties, including producing bacteriocin called plantaricin. This study aimed to detect the gene encoding bacteriocin produced by Lactobacillus plantarum BP102, and to evaluate the bacteriocin activity at each stage of partial purification. After the end of the log phase of L. plantarum BP102 was determined, and the bacteriocin-encoding genes were checked by PCR technique. Partial purification of bacteriocin was elucidated including pH-neutralized cell-free-supernatant (CFS), precipitation using 80% of ammonium sulfate, and dialysis (cut-off 10 kDa), then the bacteriocin activity in every partial purification stage was evaluated. The molecular weight of plantaricin was estimated using SDS-PAGE analysis. Lactobacillus plantarum BP102 harbored the gene encoding plantaricin (pln) biosynthesis, namely plnEF and plnK genes. The activity of crude bacteriocin was inactivated by the presence of proteinase-K enzyme. The protein concentration was gradually decreased along with the purification process. The bacteriocin activity was demonstrated at each step of the purification process (CFS, precipitation, and dialysis) against Bacillus cereus by 9.23 ± 0.20 mm, 7.86 ± 0.15 mm, and 7.6 ± 0.10 mm, respectively; while, Escherichia coli by 10.3 ± 0.55 mm, 7.4 ± 0.1 mm, and 6.86 ± 0.45, respectively. The molecular weight of partially purified bacteriocin BP102 was found to be approximately 15.9 kDa. The overlaid part of the gel showed a slight inhibition against E. coli due to a low protein concentration. This bacteriocin purification process should be further optimized to improve the bacteriocin activity that could be useful for food preservation.